Risk factors for late-onset neutropenia after rituximab treatment of B-cell lymphoma. Issue 4 (May 2015) - Arai, Yasuyuki; Yamashita, Kouhei; Mizugishi, Kiyomi; Nishikori, Momoko; Hishizawa, Masakatsu; Kondo, Tadakazu; Kitano, Toshiyuki; Kawabata, Hiroshi; Kadowaki, Norimitsu; Takaori-Kondo, Akifumi
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives Late-onset neutropenia after rituximab (RTX) therapy (R-LON) has been widely reported, but clinical studies on a large number of cases are limited. In this study, we aimed to investigate the incidence and risk factors of R-LON. Patients and methods In this study, we retrospectively analyzed data of 213 enrolled B-cell lymphoma patients (male 114; female 99) treated with RTX at a single institution. R-LON was defined as otherwise unexplained grade III–IV neutropenia after RTX. The median age of the patients was 62 years, and 129 of them were initially diagnosed at advanced stages (stage III–IV). Results R-LON occurred in 19 patients within a median of 121 (range, 49–474) days after the last RTX administration. The 1-year cumulative incidence was 9.0%. On univariate analysis, older age (>60 years), advanced stage, and purine analog or methotrexate administration were significant or borderline significant risk factors for R-LON, whereas sex, disease type, bone marrow invasion, combination with cytotoxic chemotherapeutic drugs, intensified therapy (compared with R-CHOP), prior autologous transplantation, and repeated RTX administration were not. On multivariate analysis, older age (hazard ratio (HR), 2.95) and advanced stage (HR, 3.56) were significant risk factors. Treatment with granulocyte colony-stimulating factor was feasible in grade IV R-LON patients with high risk of infection. Discussion and conclusion Careful follow-up is therefore necessary after B-cell lymphoma treatment, especially in high-risk patients with advanced disease or of older age.